Impact of the implementation of the tailings management protocol on tailings dam risk management at Huaron mine, 2021 - Velásquez Méndez, Erick Jesús (2023)
The general objective of the study was to determine the impact of the implementation of the tailings management protocol on the risk management of the tailings dam. Methodologically, it was an applied research, explanatory level, non-experimental design, longitudinal section. The sample was six failure mode analyses. The results show the difference before and after the implementation of the tailings management protocol; Before implementation the probability of occurrence was rare at 33.3%; and then the probability of occurrence is rare (83.3%). The difference in the consequence of the occurrence of the detected failures is that before implementation, the majority of the detected failures were catastrophic in nature (66.7%); and then in most failures it is (0.00%). And the difference in the level of risk in the tailings dam is that before implementation it was high (33.3%); and then it is high (0.00%). In conclusion, it has been shown that the impact of the implementation of the tailings management protocol is significant in the risk management of the tailings dam at Pan American Silver Huaron, 2021. (p<0.05).